The Dissemination of Aswaja Teachings Through the Study of RisᾹlah Ahlissunnah Waljama‘Ah Book - Ilyas, Moh (Journal of Education and Religious Studies, 2023)
This journal discusses various strategies in disseminating Aswaja, as an effort to strengthen faith in the midst of the rise of sects that are considered deviant. This research uses a qualitative approach with a case study type, using interviews, observation, and documentation as data collection techniques. The results showed that the dissemination of Aswaja was carried out through educational institutions by exploring Aswaja values in the book of Risᾱlah Ahlussunnah waljamᾱ'ah. Learning involves supporting and inhibiting factors, with stages of internalization of Aswaja values. The implication is that students are able to apply, follow the teachings of scholars, practice Islam and Indonesia, and have a moderate, balanced, and tolerant attitude.